New inequalities of Simpson’s type for differentiable functions via generalized convex function - Shan E. Farooq (2022)
This article presents some new inequalities of Simpson’s type for differentiable functions by using (α,m)-convexity. Some results for concavity are also obtained. These new estimates improve on the previously known ones. Some applications for special means of real numbers are also provided.